Efficacy of Virtual Reality as a Treatment Modality on Preoperative vs Postoperative Patient Anxiety: A Systematic Review - Faris S. S. Aldobekhi (Journal of Pharmacy and Bioallied Sciences)
Background: This systematic review aimed to investigate the efficacy of VR as a treatment modality on preoperative vs postoperative patient anxiety. Methods: A thorough search was performed over seven databases using Boolean operators and MeSH terms. Studies that used VR interventions and measured anxiety outcomes were included in the review. Results: The included studies seem to indicate that VR interventions could help to decrease anxiety in surgical patients. Most of the studies reported significant decreases in anxiety scores or improved anxiety outcomes for their VR groups as compared to control groups or standard care groups. Specifically, preoperative and postoperative anxiety scores were found to be significantly lower in VR groups compared to control groups. Conclusion: The combined results of the studies do imply that VR interventions have a positive effect on decreasing anxiety in surgical patients. Although some studies demonstrated a consistent pattern of results, others exhibit differences in their findings, which may be attributed to differences in study design, population, or intervention protocols.